2018
DOI: 10.1002/rev3.3121
|View full text |Cite
|
Sign up to set email alerts
|

Reading Recovery's unrecovered learners: Characteristics and issues

Abstract: Reading Recovery (RR) was developed in New Zealand in the early 1980s to provide 30 minutes of daily individualised literacy instruction over 20 weeks for students struggling with learning to read after one year of formal schooling. Considerable research has been undertaken on the RR programme. While results indicate short-term success for some students, each year 15-30% of students do not successfully complete the programme and are therefore 'unrecovered'. Research on the characteristics of these unrecovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Unfortunately, inappropriate forms of reading intervention operate within some RTI programmes and more extensive training of both class and specialist teachers to teach reading effectively will be fundamental to successful RTI practice (Moats, 2017). In particular, programmes that are underpinned by whole language theories, such as Reading Recovery, are unlikely to prove helpful to those who experience greatest difficulty in learning to read (Chapman & Tunmer, 2019). Such programmes typically place less emphasis upon structured, systematic phonics, and instead focus upon meaning-making and multi-cuing approaches (see Castles et al, 2018;Elliott & Grigorenko, 2014) for a detailed discussion of the longstanding 'Reading Wars' between proponents of these differing approaches.…”
Section: How Can We Best Help All Struggling Readers?mentioning
confidence: 99%
“…Unfortunately, inappropriate forms of reading intervention operate within some RTI programmes and more extensive training of both class and specialist teachers to teach reading effectively will be fundamental to successful RTI practice (Moats, 2017). In particular, programmes that are underpinned by whole language theories, such as Reading Recovery, are unlikely to prove helpful to those who experience greatest difficulty in learning to read (Chapman & Tunmer, 2019). Such programmes typically place less emphasis upon structured, systematic phonics, and instead focus upon meaning-making and multi-cuing approaches (see Castles et al, 2018;Elliott & Grigorenko, 2014) for a detailed discussion of the longstanding 'Reading Wars' between proponents of these differing approaches.…”
Section: How Can We Best Help All Struggling Readers?mentioning
confidence: 99%
“…Presently the conversation centres on the Ministry of Education's (2022, March) release of a new strategy for literacy and communication and report from The Education Hub on the perilous state of children's literacy (Hood & Hughson, 2022). There is a history of debate in Aotearoa New Zealand on the best way to teach reading (Chapman & Tunmer, 2019;McNaughton, 2020), and when people holding different viewpoints interact discussion can become quite heated. 1 While differences in perspective on literacy instruction and the achievement of school aged children are embedded in the psyche of schools in Aotearoa New Zealand, having researched reading for pleasure for over two years we have noticed that nationally very little attention in public discourse and research is given to children's reading that is interest-based or for enjoyment (Boyask et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Some older struggling readers have experienced the Reading Recovery programme in their early schooling (18.4% in the present study) and are what Chapman and Tunmer (2019) call 'unrecovered'. As noted previously, wider gaps between the struggling readers and their typically-progressing peers require longer and more intensive interventions (Roberts et al, 2008).…”
Section: Chapter 5: Study Two: the Impact Of Word Level Instruction O...mentioning
confidence: 63%
“…The lack of evidence for its efficacy has called Reading Recovery into question as an appropriate intervention for younger children (see e.g. Chapman & Tunmer, 2019;Reynolds et al, 2009). Even so, in 2007 the What Works Clearinghouse, a body that evaluates educational programs and interventions based on evidence from randomised control and quasi-scientific studies, investigated research on the effectiveness of Reading Recovery and reported positive findings.…”
Section: Reading Recovery Interventionmentioning
confidence: 99%
See 1 more Smart Citation